An Outline of Building a Lexical Database for the Armenian Language - HAKOBYAN, FRIDA (Bulletin of Yerevan University B: Philology, 2021)
This article describes the suggested principles of the construction, a freely-available lexical database for the Armenian language by using types of meaning representations based on other electronic dictionaries and various lexical databases. It is noted that a newly constructed lexical database will be a valuable resource and will heve different kinds of applications.
Keywords: computational linguistics, lexicography, computational lexicography, electronic lexicography, dictionary, electronic dictionary, database, lexical database